Re: Outstanding design conditions as of 27 April, 2020 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of conceptual design of swimming pool of BRACU new campus project.